2023
DOI: 10.21203/rs.3.rs-2429210/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximate chemical analysis and effect of age and height of Oxytenanthera abyssinica on fiber morphology and chemical compositions for pulp and paper production potential

Abstract: This study examined the chemical composition, fiber morphology, and physical properties of Oxytenanthera abyssinica culm to assess its pulping potential. TAPPT and Franklin's methods have been used for experiments. The statistical analysis showed that the chemical composition of Oxytenanthera abyssinica is influenced by the age of the plant.The amount of cellulose in the culm increases with age, while ash and extractive content decrease with an increase in age. Thethree-year agedaverage chemical content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…These results align with findings reported in other studies, which showed that presence of lignins in starch/pectin blend films [58] and carboxymethyl cellulose-lignin enhanced the antioxidant activity of the matrix [67]. Antioxidant activity of 88.74% was evidenced by Worku et al [68] after adding lignins nanoparticles to polyvinyl alcohol/chitosan films, which was slightly higher, as compared to the achieved value for OPL-11% in this work. Lignins generally exhibited a similar effect on the antioxidant activity of the films in previous studies, and variations in the obtained values may be attributed to differences in the lignin extraction processes used in various studies and the resulting lignin structures [69].…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…These results align with findings reported in other studies, which showed that presence of lignins in starch/pectin blend films [58] and carboxymethyl cellulose-lignin enhanced the antioxidant activity of the matrix [67]. Antioxidant activity of 88.74% was evidenced by Worku et al [68] after adding lignins nanoparticles to polyvinyl alcohol/chitosan films, which was slightly higher, as compared to the achieved value for OPL-11% in this work. Lignins generally exhibited a similar effect on the antioxidant activity of the films in previous studies, and variations in the obtained values may be attributed to differences in the lignin extraction processes used in various studies and the resulting lignin structures [69].…”
Section: Antioxidant Activitysupporting
confidence: 92%